Effects of Alkalinization and Rehydration on Plasma Potassium Concentrations in Neonatal Calves with Diarrhea. (29th January 2015) - Trefz, F.M.; Lorch, A.; Zitzl, J.; Kutschke, A.; Knubben‐Schweizer, G.; Lorenz, I.
Abstract : Background: Increased plasma potassium concentrations (K + ) in neonatal calves with diarrhea are associated with acidemia and severe clinical dehydration and are therefore usually corrected by intravenous administration of fluids containing sodium bicarbonate. Objectives: To identify clinical and laboratory variables that are associated with changes of plasma K + during the course of treatment and to document the plasma potassium‐lowering effect of hypertonic (8.4%) sodium bicarbonate solutions. Animals: Seventy‐one neonatal diarrheic calves. Methods: Prospective cohort study. Calves were treated according to a clinical protocol using an oral electrolyte solution and commercially available packages of 8.4% sodium bicarbonate (250–750 mmol), 0.9% saline (5–10 L), and 40% dextrose (0.5 L) infusion solutions. Results: Infusions with 8.4% sodium bicarbonate solutions in an amount of 250–750 mmol had an immediate and sustained plasma potassium‐lowering effect. One hour after the end of such infusions or the start of a sodium bicarbonate containing constant drip infusion, changes of plasma K + were most closely correlated to changes of venous blood pH, plasma sodium concentrations and plasma volume ( r = −0.73, −0.57, −0.53; P < .001). Changes of plasma K + during the subsequent 23 hours were associated with changes of venous blood pH, clinical hydration status (enophthalmos) and serum creatinine concentrations ( r = −0.71, 0.63, 0.62; P < .001). Conclusions and Clinical Importance: This study emphasizes the importance of alkalinization and the correction of dehydration in the treatment of hyperkalemia in neonatal calves with diarrhea.